2021
DOI: 10.1029/2020jg005907
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thermal Stratification on Seasonal Net Ecosystem Production and Dissolved Inorganic Carbon in a Shallow Subtropical Lake

Abstract: Small lakes (lake area < 0.1 km 2 ) occupy 25%-35% of the total area of all lakes in the world (Downing et al., 2006;Verpoorter et al., 2014). However, C emissions from small lakes are usually ignored when evaluating C fluxes (Cole et al., 2007;Raymond et al., 2013), resulting in an underestimation of CO 2 emissions on a global scale (Downing et al., 2006;Verpoorter et al., 2014). Lake size has also been revealed to be one of the most critical factors controlling CO 2 emissions, with small lakes having more co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…While studies on freshwater carbon are still limited, results indicating its potential have been revealed in recent years. For example, Lin et al (2021); Lin et al (2022) showed that pCO 2 partial pressure can be lower than that of the atmosphere throughout the year in freshwater lakes above mesotrophic levels, indicating the feasibility of freshwater carbon through the planting of water plants. Additionally, Gu et al (2020) revealed the high possibility of carbon capture and storage by Phragmites australis (common reed) in a St. Lawrence Estuary Marsh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies on freshwater carbon are still limited, results indicating its potential have been revealed in recent years. For example, Lin et al (2021); Lin et al (2022) showed that pCO 2 partial pressure can be lower than that of the atmosphere throughout the year in freshwater lakes above mesotrophic levels, indicating the feasibility of freshwater carbon through the planting of water plants. Additionally, Gu et al (2020) revealed the high possibility of carbon capture and storage by Phragmites australis (common reed) in a St. Lawrence Estuary Marsh.…”
Section: Discussionmentioning
confidence: 99%
“…The target areas of BC research have mainly focused on marine and coastal ecosystems, with less attention paid to inland waters where dense submerged aquatic vegetation exists. However, Lin et al (2022) revealed that ecosystems, such as phytoplankton in a subtropical mountainous shallow lake, capture and accumulate carbon through photosynthesis even though terrestrial carbon is supplemented through inflows and autochthonous carbon is produced (Lin et al, 2021). Freshwater areas (5.0 million km 2 ) are larger than coastal areas (1.8 million km 2 ) and are expected to have greater potential for carbon sequestration (Downing et al, 2006;Verpoorter et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…a k -empirical parameter related to lake surface area A l (km 2 ) and N 2 -Brunt-Väisälä stability frequency [s −2 ] calculated from lake water density (ρ) for different depths in the water column (z) (Lin et al, 2021)…”
Section: Discussionmentioning
confidence: 99%
“…N 2 –Brunt‐Väisälä stability frequency [s −2 ] calculated from lake water density ( ρ ) for different depths in the water column ( z ) (Lin et al., 2021) N2=gρ·ρz ${N}^{2}=-\frac{g}{\rho }\cdot \frac{\partial \rho }{\partial z}$ …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that SAV enhances the stratification of the water column (Nakayama, Sato, et al., 2020), suppressing vertical water exchange in shallow water areas (Ghisalberti & Nepf, 2006, 2009). When stratification occurs, large amounts of dissolved inorganic carbon (DIC) can accumulate in the deeper layers of an aquatic ecosystem because the dampening of vertical mixing prevents the flux of carbon between the upper and lower layers (Lin et al., 2021, 2022). Therefore, by suppressing vertical water exchange, SAV presence can limit the supply of carbon dioxide from bottom waters to the surface layer where it is subject to exchange with the atmosphere, and this effect will vary between different environments depending on the amount and form of the biomass.…”
Section: Introductionmentioning
confidence: 99%